Insect metamorphosis : from natural history to regulation of development and evolution - Belles, X. (Academic Press, an imprint of Elsevier, 2020)
Insect Metamorphosis: From Natural History to Regulation of Development and Evolution explores the origin of metamorphosis, how it evolved, and how it is it regulated. The book discusses insect metamorphosis as a key innovation in insect evolution. With most of the present biodiversity on Earth composed of metamorphosing insects--approximately 1 million species currently described, with another 10-30 million still waiting to be discovered, the book delves into misconceptions and past treatments. In addition, the topic of integrating insect metamorphosis into the theory of evolution by natural selection as noted by Darwin in his On the Origin of Species is also discussed.